Encapsulating Sulfur into Hierarchically Ordered Porous Carbon as a High‐Performance Cathode for Lithium–Sulfur Batteries. Issue 3 (23rd November 2012) - Ding, Bing; Yuan, Changzhou; Shen, Laifa; Xu, Guiyin; Nie, Ping; Zhang, Xiaogang
Abstract A three‐dimensional (3D) hierarchical carbon–sulfur nanocomposite that is useful as a high‐performance cathode for rechargeable lithium–sulfur batteries is reported. The 3D hierarchically ordered porous carbon (HOPC) with mesoporous walls and interconnected macropores was prepared by in situ self‐assembly of colloidal polymer and silica spheres with sucrose as the carbon source. The obtained porous carbon possesses a large specific surface area and pore volume with narrow mesopore size distribution, and acts as a host and conducting framework to contain highly dispersed elemental sulfur. Electrochemical tests reveal that the HOPC/S nanocomposite with well‐defined nanostructure delivers a high initial specific capacity up to 1193 mAh g−1 and a stable capacity of 884 mAh g−1 after 50 cycles at 0.1 C. In addition, the HOPC/S nanocomposite exhibits high reversible capacity at high rates. The excellent electrochemical performance is attributed exclusively to the beneficial integration of the mesopores for the electrochemical reaction and macropores for ion transport. The mesoporous walls of the HOPC act as solvent‐restricted reactors for the redox reaction of sulfur and aid in suppressing the diffusion of polysulfide species into the electrolyte. The "open" ordered interconnected macropores and windows facilitate transportation of electrolyte and solvated lithium ions during the charge/discharge process. These results show that nanostructured carbon with hierarchical pore distribution could be a promising scaffold for encapsulating sulfur to approach high specific capacity and energy density with long cycling performance.